Populism and Carbon Tax Justice: The Yellow Vest Movement in France. (18th August 2021) - Driscoll, Daniel
Abstract: Scholars cite right-wing authoritarian and business-elite influences in their explanations of populist mobilization against climate reforms. The Yellow Vest movement in France, initially sparked by opposition to a carbon tax, defies the generalizations offered by scholars, the media, and politicians alike. This populist movement emerged from below rather than from elite sponsorship and was motivated by social justice concerns. Through in-depth interviews with 31 Yellow Vest activists as well as supplementary primary texts and data, I uncover how the activists frame carbon taxation and climate change within their political struggle. The findings are four-fold: 1) the Yellow Vests are concerned about global climate change and feel their anti-climate depictions in the media are rooted in a government strategy to divide and discredit the movement; 2) they view the government's taxing them in order to fight climate change as corrupt and unfair; 3) they argue that the carbon tax is additionally unjust due to their precarity, which has increased over several decades; 4) they want to fight climate change on their own terms and argue for more direct forms of democracy to equalize decision making. I conclude with a framework for understanding how and why popular movements oppose climate reforms.